Research and Development on Metal Hydride Heat Pump/Air Conditioning Systems - 李刚; 刘华军; 李来风; 杨柯; 杜屏; 吕曼祺 (Zhileng xuebao)
The metal hydride heat pump /air conditioning (MHHP/AC) system is a new technique of energy conservation and environmental protection. The operating principle, feature and advantage of the MHHP/AC systems are stated. The history and status of experimental and theoretical studies on the MHHP/AC are described. Some published literatures on MHHP/AC systems are summarized. How to enhance the performance of the hydrogen storage alloys and the heat transfer on the MHHP/air conditioning systems are analyzed. Numerical simulation research on the MHHP/AC is reviewed.